Smart GrowTech: IoT-Based Monitoring System untuk Atasi Ketidakstabilan Produksi dan Pengembangan Community-Based Agribusiness di Kelompok Tani Jamur Tiram Nagari Taram - Febtriko, Anip; Hasri Awal; Tri Rahayuningsih (Jurnal Pengabdian Masyarakat, 2025)
The Nagari Taram Oyster Mushroom Forest Farmers Group, Lima Puluh Kota Regency, West Sumatra, faces serious challenges in the form of production instability and weak community-based agribusiness management. The main problems identified include uncontrolled mushroom house environmental management, high levels of contamination of growing media, and dependence on middlemen without diversification of processed products. This community service program offers innovative solutions through the implementation of Smart GrowTech, an Internet of Things (IoT)-based monitoring system to control temperature, humidity, and CO₂ levels in real-time, as well as the integration of the JamurLink application as a digital platform for monitoring and harvest prediction. In addition, the Auto-Steril innovation is used to increase the effectiveness of planting media sterilization to reduce contamination to below 5%. In the agribusiness aspect, the program is designed to strengthen the farmer group's institutions through business management training, digital marketing, product diversification (chips, shredded meat, mushroom nuggets), and strengthening e-commerce-based marketing networks. Targets include a 40–60% increase in productivity, an increase in farmer income from IDR 2–3 million to IDR 5–7 million per month, the establishment of a farmer cooperative, and the replication of the technology to other farmer groups. With a precision technology approach and community empowerment, this program is expected to improve the sustainability of local agribusiness, support food security, and contribute to the achievement of SDGs 1, 2, 8, and 9.